Contribution à la connaissance des modes de dislocation et de destruction du squelette pendant la crémation : l’apport du bûcher funéraire en fosse du Néolithique final à Reichstett-Mundolsheim (Bas-Rhin) - Frédérique Blaizot (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
An archaeological excavation carried out on the site of Reichstett-Mundolsheim, near Strasbourg, produced a circular pit dated to the beginning of the Late Neolithic period which contained a simultaneous primary cremation of eleven individuals. The large number of individuals compared to the size of the structure, the high fragmentation of the bones and the modifications received by some of them because of fire complicated of course the identification of each skeleton; however, several observations relating to the behavior of the various anatomical areas during the cremation could be made. We propose a discussion of certain aspects : the resistance to fire of the various anatomical areas, the problem of our theoretical references concerning weight, and the processes of dislocation of the articular connections, knowing that the type of pyre and the cremation process play a fundamental role in the fragmentation and final arrangement of the bones. The results indicate a very great variability in the state of the anatomical connections and in the conservation of the bones, whereas the conditions of cremation are the same for all the skeletons. So it is difficult to identify the etiology of the alteration of the anatomical connections. Lastly, it appears that natural processes of destruction can cause certain phenomena which we may interpret as significant funerary features.